Multiple‐Stimulus‐Responsive Supramolecular Gels and Regulation of Chiral Twists: The Effect of Spacer Length. Issue 20 (1st April 2015) - Miao, Wangen; Yang, Dong; Liu, Minghua
Abstract A new class of homologous gelators, LG12‐(CH2)n‐BSA, composed of bipyridinyl groups, L‐glutamic moieties having double dodecyl chains, and linked alkyl spacers with different lengths were synthesized. It was found that these gelators could immobilize medium‐polarity solvents readily and the behaviors of these gels showed a dependence on the spacer length. Of all the gels, the LG12‐(CH2)11‐BSA gels exhibited self‐healing property and multiple‐stimulus responsibility, such as heating, shaking, and sonication. The investigation of CD spectra indicated that the supramolecular chirality, which was attributed to the chiral transfer from the chiral center to the assemblies, was also closely related to the length of methylene spacers. The longer the alkyl spacers, the weaker the transmitted supramolecular chirality. Only LG12‐(CH2)1‐BSA gelators, which had the shortest spacers, formed right‐handed nanoscale chiral twists owing to crowded hydrogen bonding interactions. Moreover, the high‐polarity solvent DMF was found to be able to regulate the chiral twist as well as its pitch length readily.